EFFECTS OF IMMUNOTROPIC PREPARATIONS ON ACTIVITY OF LYMPHOCYTES’ MEMBRANE ENZYMES UNDER RATE INPUT DOXORUBICIN - Москвичов Є. П.; Рожковський Я. В. (World of Medicine and Biology, 2014)
In experiments on 228 outbred rats studied the dynamics of changes in the activity of enzymes membran adenosine deaminase (ADA) and 5’-nucleotidase (5’-NK) lymphocytes in the mesenteric lymph nodes on the background of a course of administration of doxorubicin and the prophylactic use of immunomodulators amixin, imunofan and polyoxidonium. Established that the course administration of doxorubicin at a dose of 5 mg / kg resulted in a multidirectional changes the activity of ADA and 5’-NK. The most pronounced changes in the enzymatic activity of lymphocytes develop after 4 single administration of cytostatic and prophylactic amixin, immunofan and polyoxidonium and reduces the severity of such violations. It is shown that immunomodulator polioxidonium most radically reduces doxorubicin-induced activity of ADA violations and 5’-NK lymphocytes, which indicates its more pronounced membrane-protective properties.